PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI 2 BEBENGAN KECAMATAN BOJA - Ambar Sekti; Noor Miyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of writing this scientific article is to find out, explain and analyze the role of school principals in improving the quality of school education at SDN 2 Bebengan, Boja District. The method used in writing this scientific article uses case studies through observation. Data was collected through text studies and relevant research results. Data analysis is carried out in the following steps: First, the data that has been collected is classified based on the formulation of the problem being studied. Second, the data studied qualitatively was analyzed using content analysis. Third, based on the results of data analysis and interpretation, conclusions are drawn which are accompanied by suggestions. Based on the description above, it can be said that the role of the principal in improving the quality of education is in the good category and has a positive influence on the quality of schools at SDN 2 Bebengan, Boja District, Kendal Regency. This shows that the better the role of the principal, the more the quality of school education will improve.